Drone application with low-cost remote-controlled earth-drilling machine for modern agriculture - Samseemoung, Grianggai; Thongindam, Puttapon; Soni, Peeyush (Agriculture and Natural Resources, 2023)
Importance of the work: Drilling can be modeled using an up-and-down drive algorithm, controlling an 18 V, wireless, hand-held drill. When the radio-controlled drill rotates counterclockwise, the earth drilling machine moves downward along the spiral axis, creating a drill hole. Objectives: To design and fabricate a drone with a low-cost, remote-controlled, earth-drilling machine for use in modern agriculture. Materials & Methods: A drone was designed and created with a body and driving system using an Arduino board and motor drive module design. A system was developed to control the up and down movement of the drill to make holes remotely. The working speed (in kilometers per hour) and its impact on working capacity (in hectares per hour) were assessed, including fuel consumption (in liters per hour) and electricity consumption (in kilowatt hours) Results: With an increase in working speed, both fuel and electricity consumption increased. At a working speed of 0.04 km/hr, the fuel consumption was 0.5 L/hr, resulting in electricity consumption of 0.541 kWhr and a working capacity of 0.05 ha/hr. A crosscomparison of the readings from the soil compaction meter revealed a good correlation between the working capacity trend for clay soil and loamy soil. Main finding: The developed specially designed earth-drilling machine for modern agriculture could drill holes in real time with a system for controlling the drilling up and down position using a remote control. Soil compaction maps at (3 mth and 6 mth) were developed using the ArcGIS® software.